Mul Toothbrush / Nur Alis Narjiwa Ali - Ali, Nur Alis Narjiwa (2020)
Mul Toothbrush will provide 3 in 1 electric toothbrush which are combination of a tongue scraper, fountain rinse and space or storage to put a toothpaste. A tongue scraper that helps users clean their tongue after brushing their teeth. Next, having a toothpaste storage where they can refill the toothpaste and use it when they want to brush their teeth also Mul Toothbrush comes with fountain rinse, it will clean the rest of the toothpaste left in the mouth after brushing. The main reason that make this Mul Toothbrush are to create a multipurpose of electric toothbrush for tongue and teeth also to make it easier saves users time when brushing their teeth. Mul toothbrush also came with inductive wireless charge, when the user places the toothbrush inside the charger box, the magnetic field causes the current to flow into the other coil, which connects to the battery.